2013
DOI: 10.1111/ans.12311
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the value and impact of the Victorian Audit of Surgical Mortality

Abstract: Introduction: Since the Victorian Audit of Surgical Mortality (VASM) commenced in 2007, 95% of Victorian Fellows have agreed to participate and have provided data on the deaths of patients receiving surgical care. All public, and the majority of private, hospitals involved in the delivery of surgical services in Victoria have been submitting data on deaths associated with surgery. De-identified reports on this data are distributed in regular annual reports and case note review booklets. Although informal feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
(5 reference statements)
0
12
0
Order By: Relevance
“…The findings indicated that data collected through VASM could be translated into improvements in the quality and safety of patient care which had attained a robust and mature status. A concordance study confirmed that there was good agreement between first and second line assessors, as well as detecting a higher detection rate of clinical management issues by either assessor compared with the treating surgeon, thus validating the audit processes 18 19…”
Section: Discussionmentioning
confidence: 59%
“…The findings indicated that data collected through VASM could be translated into improvements in the quality and safety of patient care which had attained a robust and mature status. A concordance study confirmed that there was good agreement between first and second line assessors, as well as detecting a higher detection rate of clinical management issues by either assessor compared with the treating surgeon, thus validating the audit processes 18 19…”
Section: Discussionmentioning
confidence: 59%
“…It is also important to evaluate an activity such as VASM by an external ‘audit of the audit’, which was performed in 2011 by an independent consultancy company. This evaluation concluded that VASM processes were robust and mature after extensive consultation with stakeholders and independent scrutiny of data …”
Section: Discussionmentioning
confidence: 98%
“…This evaluation concluded that VASM processes were robust and mature after extensive consultation with stakeholders and independent scrutiny of data. 4 Attainment of 100% hospital participation has been an aim since inception and this was realized in 2012. Changes to CPD requirements by the RACS have also improved the participation rate of Fellows, as it is now compulsory.…”
Section: Discussionmentioning
confidence: 99%
“…23 The Victorian Audit of Surgical Mortality prompted a third of its surgeons to implement changes. 24 The wider influence of audits (the Hawthorne effect) is well recognized. 25 The individual feedback in ANZASM is the fundamental difference from other audits.…”
Section: Discussionmentioning
confidence: 99%